Solution NMR structure of the major cold shock protein (CspA) from Escherichia coli: identification of a binding epitope for DNA. - Newkirk, K (1994)
Sequence-specific 1H and 15N resonance assignments have been determined for the major cold shock protein (CspA) from Escherichia coli with recently developed three-dimensional triple-resonance NMR experiments. By use of these assignments, five antiparallel beta-strands were identified from analysis of NMR data. Strands 1-4 have a classical 3-2-1-4 Greek key beta-sheet topology and there are two beta-bulges, at positions Lys10-Trp11 and Gly65-Asn66. Three-dimensional structures of CspA were generated from NMR data by using simulated annealing with molecular dynamics. The overall chain fold of CspA is a beta-barrel structure, with a tightly packed hydrophobic core. Two-dimensional isotope-edited pulsed-field gradient 15N-1H heteronuclear single-quantum coherence spectroscopy was used to characterize the 15N-1H fingerprint spectrum with and without a 24-base oligodeoxyribonucleotide, 5'-AACGGTTTGACGTACAGACCATTA-3'. Protein-DNA complex formation perturbs a subset of the amide resonances that are located mostly on one face of the CspA molecule. This portion of the CspA molecular surface includes two putative RNA-binding sequence motifs which contribute to an unusual cluster of eight surface aromatic side chains: Trp11, Phe12, Phe18, Phe20, Phe31, His33, Phe34, and Tyr42. These surface aromatic groups, and also residues Lys16, Ser44, and Lys60 located on this same face of CspA, are highly conserved in the family of CspA homologues. These isotope-edited pulsed-field gradient NMR data provide a low-resolution mapping of a DNA-binding epitope on CspA.